2004
DOI: 10.1073/pnas.0303842101
|View full text |Cite
|
Sign up to set email alerts
|

LacZ -expressing olfactory ensheathing cells do not associate with myelinated axons after implantation into the compressed spinal cord

Abstract: Studies have shown that implanting olfactory ensheathing cells (OECs) may be a promising therapeutic strategy to promote functional recovery after spinal cord injury. Several fundamental questions remain, however, regarding their in vivo interactions in the damaged spinal cord. We have induced a clip compression injury at the T10 level of the spinal cord in adult rats. After a delay of 1 week, OECs isolated from embryonic day 18 rats were implanted into the cystic cavity that had formed at the site of injury. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
72
1

Year Published

2004
2004
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(78 citation statements)
references
References 53 publications
5
72
1
Order By: Relevance
“…Takami et al (2002) reported that SC but not OEC transplantation results in improved hindlimb locomotor function. Moreover, although numerous reports suggest that OECs can form myelin when transplanted into the demyelinated (Franklin et al, 1996;Imaizumi et al, 1998;Barnett et al, 2000;Kato et al, 2000;Akiyama et al, 2004;Radtke et al, 2004) or injured (Li et al, 1997(Li et al, , 1998Imaizumi et al, 2000a,b) spinal cord, a recent study was unable to find evidence of OEC myelination in the compressed spinal cord and suggests that OEC transplantation may facilitate endogenous SC invasion into the lesion site (Boyd et al, 2004). OECs in culture are diverse and exhibit characteristics of astrocytes, SCs, and oligodendrocytes.…”
Section: Introductionmentioning
confidence: 95%
“…Takami et al (2002) reported that SC but not OEC transplantation results in improved hindlimb locomotor function. Moreover, although numerous reports suggest that OECs can form myelin when transplanted into the demyelinated (Franklin et al, 1996;Imaizumi et al, 1998;Barnett et al, 2000;Kato et al, 2000;Akiyama et al, 2004;Radtke et al, 2004) or injured (Li et al, 1997(Li et al, , 1998Imaizumi et al, 2000a,b) spinal cord, a recent study was unable to find evidence of OEC myelination in the compressed spinal cord and suggests that OEC transplantation may facilitate endogenous SC invasion into the lesion site (Boyd et al, 2004). OECs in culture are diverse and exhibit characteristics of astrocytes, SCs, and oligodendrocytes.…”
Section: Introductionmentioning
confidence: 95%
“…While the precise mechanism of this functional recovery is not fully understood, several mechanisms have been suggested including remyelination (Devon and Doucette, 1992;Franklin et al, 1996;Imaizumi et al, 1998;Sasaki et al, 2004), long axon tract regeneration (Li et al, 1997;Ramon-Cueto et al, 2000;, axonal sparing (Plant et al, 2002) and plasticity associated with novel polysynaptic pathways (Keyvan-Fouladi et al, 2002;Bareyre et al, 2004). In addition, recruitment of endogenous SCs (Takami et al, 2002;Boyd et al, 2004;Ramer et al, 2004) and remote inhibition of apoptosis of motor cortical neurons (Sasaki et al, 2006a) have been suggested to contribute to improvement in functional outcome in injured spinal cord after OEC transplantation.…”
Section: Introductionmentioning
confidence: 99%
“…260 On a final note, OECs and SCs may share the stage: recent work from our group demonstrates that OEC transplantation enhances invasion of host SCs into the injured spinal cord. 246 This finding is especially significant in light of recent data indicating that myelin within OEC grafts is SC-, not OEC-derived 261 (discussed in the subsequent section below). Whether the observed axonal growth and/or functional recovery after SCI can be attributed to the presence of grafted OECs or might also be due to infiltrating host SCs remains to be seen.…”
Section: Scs and Oecs: A Duel Or A Duet?mentioning
confidence: 86%